Meniscal Injuries: Mechanism and Classification. Issue 3 (September 2021) - Wells, Matthew E.; Scanaliato, John P.; Dunn, John C.; Garcia, E'Stephan J.
Abstract : Meniscal tears may be managed through conservative physical therapy and nonsteroidal anti-inflammatory medications or operative intervention. Meniscal repair is superior to partial meniscectomy with better functional outcomes and less severe degenerative changes over time. Surgical advances in operative techniques, modern instrumentation and biological enhancements collectively improve healing rates of meniscal repair. However, failed repair is not without consequences and can negative impact patient outcomes. Therefore, it is imperative for surgeons to have a thorough understanding of the vascular zones and biomechanical classifications of meniscal tears in order to best determine the most appropriate treatment.